Factors Affecting Product Purchase Decisions with Religiosity as a Moderating Variable among Students of the Islamic Economics Study Program at UIN North Sumatra - Irwansyah, Irwansyah; Armayani Hasibuan, Reni Ria; Fadhila Rahma, Tri Inda (Management of Zakat and Waqf Journal (MAZAWA), 2025)
The rise of imported food products in Indonesia has influenced consumer interest, even though many of them do not yet have a halal label. This study aims to determine how halal literacy, halal labels, product quality, and consumer trust influence purchasing decisions for imported products. The sampling method used was non-probability sampling through the distribution of questionnaires to 90 respondents. Data analysis was conducted using a moderated regression method with the help of SPSS 22. The results showed that the halal literacy variable did not have a significant effect on purchasing decisions with a significance value of 0.087 > 0.05. Meanwhile, halal labels, product quality, and consumer trust each have a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Religiosity was only able to moderate the influence of consumer trust on purchasing decisions with a significance value of 0.038 < 0.05, while no moderating effect was found for the variables halal literacy, halal labels, and product quality